Teaching action competence in education for sustainable development – a qualitative study on teachers’ ideas, opinions, attitudes and self-conceptions - Schönstein, Robin Felix; Budke, Alexandra (Frontiers in Education, 2024)
Education for Sustainable Development (ESD) is a policy guideline which has a significant impact on the teaching of geography in Germany. A central element of this model is to impart and develop in students a goal-oriented action competence to solve sustainability problems. However, action competence in Education for Sustainable Development has not yet been scientifically defined or sufficiently researched. This raises the question of how teachers currently teach action competence to students as a central element of Education for Sustainable Development. This article examines teachers' understanding of Education for Sustainable Development, action competence and their own role in this context. To this end, a literature-based model of geographical action competence in Education for Sustainable Development is presented. Subsequently, a qualitative triangulated teacher study is presented, which is analysed with the help of the model. It is shown that teachers generally have a high level of knowledge about ESD and are highly motivated to teach action competence. However, it becomes clear that the teachers seem to differ in their understanding of sustainable action competence as well as in their understanding of their own role.